Patient satisfaction with a new skin cancer teledermatology service. (25th March 2020) - Nicholson, P.; Macedo, C.; Fuller, C.; Thomas, L.
Summary: Background: Rising numbers of two‐week‐wait (2WW) skin cancer referrals have caused increasing pressure on UK dermatology departments. Initiatives to address this include teledermatology. Previous studies have indicated good patient acceptability but most have focused on general dermatology rather than skin cancer referrals, and have taken place in rural settings, where teledermatology may be preferable. Aim: To evaluate patient satisfaction of teledermatology 2WW services in a London‐based tertiary National Health Service (NHS) setting. Methods: A literature search was performed and a patient satisfaction survey was designed to evaluate: (i) ease of completing a questionnaire about the skin lesion; (ii) lifestyle impact; (iii) preferences regarding electronic data collection and communication of results; and (iv) confidence in the service. A five‐point Likert scale was used to assess responses. The study took place over a 20‐week period. Results: Over half (51%; n  = 31 of 60 patients) were female; 78% (47) were aged ≤ 55 years and 65% (39) were Caucasian. Over 80% (49) would recommend the service, and the majority felt confident with the teledermatology model. Overall, patients would be happy to complete electronic questionnaires and receive results electronically, with younger patients being more amenable to this. Patients with better health status, those of younger age and those with less frequent visits to a dermatologist were more accepting of teledermatology. Conclusion: To our knowledge, this is the first comprehensive study evaluating patient satisfaction with teledermatology specifically for 2WW referrals in an NHS setting. As skin cancer referrals increase, dermatology departments must adjust. Patient involvement and feedback is paramount in implementing and expanding teledermatology services.